Driving Factors of Impulse Buying Tendency For Alfamart Consumers. (Case Study at Alfamart Kramas, Banyumanik, Semarang) - KIrana Jalantina, Dyah Ika; Magdalena, Maria; Rahmawati, Putri (Sean Institute, 2025)
The purpose of this research is to analyze the influence store atmosphere, product displays, bonus packs, price discounts, in-store promotions and service quality on impulse buying (unplanned purchases) among consumers at Alfamart Kramas, Tembalang, Semarang. Using multiple regression analysis method, data collection was conducted by distributing questionnaires to consumers who had made purchases or transactions at Alfamart Kramas Tembalang totaling 100 respondents as research samples. The results showed that the three independent variables, namely store atmosphere, product display, bonus pack, price discount, in-store promotional and service quality have a positive and significant effect on the dependent variable , namely impulse buying.